2012
DOI: 10.1038/nrm3350
|View full text |Cite|
|
Sign up to set email alerts
|

TFIIH: when transcription met DNA repair

Abstract: The transcription initiation factor TFIIH is a remarkable protein complex that has a fundamental role in the transcription of protein-coding genes as well as during the DNA nucleotide excision repair pathway. The detailed understanding of how TFIIH functions to coordinate these two processes is also providing an explanation for the phenotypes observed in patients who bear mutations in some of the TFIIH subunits. In this way, studies of TFIIH have revealed tight molecular connections between transcription and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
264
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 284 publications
(273 citation statements)
references
References 201 publications
4
264
0
5
Order By: Relevance
“…The genes responsible for the photosensitive form of TTD encode the XPB, XPD, and p8/TTDA subunits of the general transcription factor IIH (TFIIH). All of the mutations associated with TTD result in reduced cellular levels (8,9) and impaired functioning of TFIIH in NER and basal transcription (10)(11)(12). Furthermore, they may interfere with the role of TFIIH in transcription regulation (13)(14)(15)(16).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The genes responsible for the photosensitive form of TTD encode the XPB, XPD, and p8/TTDA subunits of the general transcription factor IIH (TFIIH). All of the mutations associated with TTD result in reduced cellular levels (8,9) and impaired functioning of TFIIH in NER and basal transcription (10)(11)(12). Furthermore, they may interfere with the role of TFIIH in transcription regulation (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Notably, premalignant skin lesions and cutaneous tumors have never been reported in TTD. It was suggested that pathological features of XP are associated with mutations that mainly affect the DNA repair activity of TFIIH, whereas those typical of TTD also impair transcription (12,(17)(18)(19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…NER은 DNA 손상을 인식하는 방법에 따라 global genome repair (GGR)와 transcription-coupled repair (TCR)의 두 가지 경로로 나누어진 다. 이 두 경로는 DNA 손상을 인식하는 초기 단계에서는 일련 의 서로 다른 단백질들이 관여하지만, 그 이후에는 DNA 손상확 인, 이중나선 풀기, 손상된 가닥 자르기 등의 공통된 단계들을 거 친다 (Prakash and Prakash, 2000;Compe and Egly, 2012).…”
unclassified
“…TFIIH 복합체에는 helicase인 Rad25와 Rad3 (각각 인간 XPB와 XPD의 orthologue)가 포함되 어 있는데, 이들은 DNA 손상부위를 확인하고 여는 역할을 한 다. 그 다음으로 또 다른 손상된 DNA 결합단백질인 Rad14 (인 간 XPA의 orthologue)과 RPA 등이 결합하여 pre-incision 복합 체를 형성한다 (Mardiros et al, 2011;Compe and Egly, 2012).…”
unclassified